The Roman Limekilns of the Bamboccianti - Levine, D.A. (The Art Bulletin, 1988)
Pieter van Laer and his followers — the so-called Bamboccianti — have usually been interpreted as realists or near-realists who painted simple, unassuming scenes of everyday life in seventeenth-century Rome. The testimony of their earliest critics gives us reason to suspect, however, that the Bamboccianti were actually pursuing a contrived form of painting that expressed meaning through irony and paradox. This idea is tested by examining one theme treated frequently by the artists in question — limekilns in Roman settings. By witty allusion to both the destruction and persistence of antiquity, pictures of Roman limekilns lead the viewer to contemplate a paradox regarding the nature of greatness and eternity. © 1988, College Art Association of America, Inc. All rights reserved.
0 citations (Crossref) [2023-10-31]
Keywords: dept.art